2021
DOI: 10.3389/fphys.2021.678863
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase-2 Interacting Protein-1 Regulates Physiological Cardiac Hypertrophy via Inhibition of Histone Deacetylase 4 Phosphorylation

Abstract: Different kinds of mechanical stimuli acting on the heart lead to different myocardial phenotypes. Physiological stress, such as exercise, leads to adaptive cardiac hypertrophy, which is characterized by a normal cardiac structure and improved cardiac function. Pathological stress, such as sustained cardiac pressure overload, causes maladaptive cardiac remodeling and, eventually, heart failure. Casein kinase-2 interacting protein-1 (CKIP-1) is an important regulator of pathological cardiac remodeling. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“… 390 CKIP‐1 regulates physiological cardiac hypertrophy by inhibiting HDAC4 phosphorylation. 391 In an AngII‐induced mouse model of pathological cardiac hypertrophy, the pan‐HDAC inhibitor (HDACI) emodin ameliorates hypertrophy by inhibiting the activity of class I, IIa, and IIb HDACs. 392 HDACs are also involved in myocardial fibrosis.…”
Section: Acetylationmentioning
confidence: 99%
See 1 more Smart Citation
“… 390 CKIP‐1 regulates physiological cardiac hypertrophy by inhibiting HDAC4 phosphorylation. 391 In an AngII‐induced mouse model of pathological cardiac hypertrophy, the pan‐HDAC inhibitor (HDACI) emodin ameliorates hypertrophy by inhibiting the activity of class I, IIa, and IIb HDACs. 392 HDACs are also involved in myocardial fibrosis.…”
Section: Acetylationmentioning
confidence: 99%
“…The interaction between SIRT1 and eNOS can activate eNOS by reducing its acetylation level, which promotes NO production and vasodilation 390 . CKIP‐1 regulates physiological cardiac hypertrophy by inhibiting HDAC4 phosphorylation 391 . In an AngII‐induced mouse model of pathological cardiac hypertrophy, the pan‐HDAC inhibitor (HDACI) emodin ameliorates hypertrophy by inhibiting the activity of class I, IIa, and IIb HDACs 392 .…”
Section: Acetylationmentioning
confidence: 99%
“…Somy Yoon et al suggested that PP2A is a critical regulator of pathological cardiac hypertrophy [ 157 ]. The inhibition of pathological cardiac hypertrophy by casein kinase-2 interacting protein-1 (CKIP-1), a regulator of cell proliferation and apoptosis and an important regulator of pathological cardiac remodeling, was achieved by increasing the dephosphorylation of histone deacetylase 4 (HDAC4) through the recruitment of PP2A, and this signaling cascade was associated with pathological hypertrophy [ 155 , 159 ]. The specific mechanisms by which PP2A exerts its antihypertrophic effects via TGF-β to regulate the development of myocardial hypertrophy and the other downstream signaling molecules involved in this signaling pathway need to be further investigated.…”
Section: Other Signaling Pathways In Pathological Cardiac Hypertrophymentioning
confidence: 99%
“…Cardiovascular diseases lead to incompatible regeneration in heart cells by increasing fibrosis and decreasing aerobic capacity. Some reports have suggested that the PI3K/AKT signaling pathway is an important regulator of cell growth that regulates cell growth and proliferation processes, gene expression, and protein synthesis (5,6). Many studies have indicated that the PI3K enzyme is activated by specific stimuli in the heart, and it plays an important role in regulating heart muscle growth by binding to tyrosine kinase receptors.…”
Section: Introductionmentioning
confidence: 99%